Particle and Cell Separation in Deterministic Lateral Displacement Arrays with Inverse L-Shaped Pillars - Hao Jiang; Fengyang Zhang; Zhou Fan; Chundong Zhang; Zunmin Zhang (Micromachines)
Deterministic lateral displacement (DLD) has emerged as a powerful microfluidic technique for label-free particle separation with high resolution. Although recent innovations in pillar geometry have broadened its biomedical applications, the fundamental mechanisms dictating flow behavior and separation efficiency remain not fully understood. In this study, we conducted dissipative particle dynamics simulations to systematically investigate the separation of rigid spherical particles and red blood cells (RBCs) in DLD arrays with inverse L-shaped pillars. The simulations established a predictive formula for the critical separation size in such devices and demonstrated that inverse L-shaped pillars enabled a reduced critical separation size compared with conventional circular pillars. Additionally, we revealed that the inverse L-shaped pillars could act as deformability sensors, promoting localized RBC deformation near their protrusions and inducing stiffness-dependent bifurcation in cell trajectories, which enables effective sorting based on cell deformability. These findings advance the mechanistic understanding of inverse L-shaped DLD arrays and provide valuable design principles for their potential applications.